Kerjasama Polri Dengan New Zealand Police Dalam Menangani Kejahatan Maritim di Indonesia : Studi Kasus Sindikat People Smuggling By Sea oleh Kapten Bram - Hardanto, Fadil Mahetza; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Maritime crime is an issue that is rife in areas of the country that have extensive waters. Indonesia is one of the countries targeted by maritime crime. One of the maritime crimes that occur using Indonesian waters is people smuggling. People smuggling is a form of transnational crime. One of the cases of human smuggling in Indonesian waters that occurred was carried out by a syndicate known as Captain Bram's syndicate. Most of the perpetrators and victims of people smuggling commit this crime because it is based on factors from their home country either because of the political or economic state of their origin countries. Countries such as New Zealand are also one of the countries used for smuggling purposes. This research was conducted with the aim of getting to know more about maritime crime, especially in the field of human smuggling. The author uses the theory of Liberalism interdependence which considers a modernization can increase the level of interdependence among States. The Police of the Republic of Indonesia and New Zealand Police conduct bilateral cooperation in maritime affairs and form a Bilateral Working Group. After conducting research using qualitative research method, researcher finds out that this collaboration did not stop in just maritime field but also continues in other fields such as counter-terrorism, drug trafficking and capacity building of police personnel.